The Effectiveness of Memrise Application to Teach English Vocabulary at Tenth Grade Students of SMK Sore Tulungagung - Amilia, Izza Apri; Dina Kartikawati (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Vocabulary is an important element in language acquisition. However, currently many students lack vocabulary knowledge and many teachers still have not implemented technology in learning. This research aims to determine the effectiveness of the Memrise application in teaching English vocabulary and the differences in students’ vocabulary mastery before and after treatment. The method used is quantitative with a pre-experimental design. Data were collected through pre-test and post-test on 35 students of class X-TSM 2 SMK Sore Tulungagung in the 2024/2025 academic year. The results showed that the average score increased from 66.14 to 86.71 after using the application. The paired t-test showed a t value of -11.031 with a significance of <0.001, which means there is a significant difference. Cohen's d effect size value of -1.865 and Hedges -1.844 showed a large effect. These results prove that the Memrise application is effective in improving students' vocabulary mastery. The implication is that application-based learning such as Memrise can be an interesting and useful alternative in the English learning process at the vocational school level